A comparison for the effects of raw, smoked, and smoked and brined areca nut extracts on the immune and inflammatory responses in the Kunming mice. Issue 8 (14th June 2020) - Li, Ke; Wang, Chuanhua; Zhao, Ziwei; Wu, Zhongqin; Wu, Zhongkun; Tian, Xing; Xiao, Yu; Li, Zongjun; Wang, Yuanliang
Abstract: Chewing of areca nuts is quite popular in various regions worldwide. Previous studies have demonstrated the pharmacological and toxicological effects of fresh areca nuts. However, processed areca nuts, which are popular in the Hunan province of China, have not been extensively studied for its biological effect. This study aimed at investigating the impact of the acrea nut extracts (ANE) prepared from the raw material, the semi‐product, and the final product on the immune system and inflammation‐related markers in the Kunming mice. The mice were assigned to seven different groups and administered different ANE at two concentrations (1X and 5X) for four weeks. Total body weight gain and organ coefficient of the liver, spleen, and kidney, as well as the immune system and inflammation‐related markers were evaluated. The results revealed that processed areca nuts have a much milder effect on the mice immune system and some inflammatory markers than fresh areca nut in the Kunming mice. Practical applications: Chewing various forms of areca nuts is popular in China, Southeast Asia, and other regions. People from Hunan, China prefer to chew a processed areca nut, which has rarely been studied. This manuscript explores the effects of three kinds of areca nut extracts on the immune system‐ and inflammation‐related indicators in Kunming mice. The obtained results revealed that processed areca nuts had significantly milder effects than the raw nut/nut extract, particularly on the body weight, immune responses, and inflammatory markers. The results of the present study provide some new directions for the areca nut industry and raise public awareness for the undesirable effects of areca nuts. Abstract : Processed areca nuts have a much milder effect on the mice immune system and some inflammatory markers than fresh areca nuts in the Kunming mice.